A quantitative real‐time PCR assay for identification and enumeration of the occasionally co‐occurring ichthyotoxic Pseudochattonella farcimen and P. verruculosa (Dictyochophyceae) and analysis of variation in gene copy numbers during the growth phase of single and mixed cultures. Issue 2 (8th March 2016) - Eckford‐Soper, Lisa K.; Daugbjerg, Niels
Abstract : The ichthyotoxic genus Pseudochattonella forms recurrent extensive blooms in coastal waters in Japan, New Zealand and Northern Europe. It comprises of two morphologically similar species, P. verruculosa and P. farcimen, which complicates visual species identification and enumeration of live and fixed material. Primers designed previously could not quantitatively distinguish species in mixed assemblages. To address this issue we developed two primer sets: one revealed itself to be genus specific for Pseudochattonella and the other species‐specific for P. verruculosa . By subtracting cell estimates for P. verruculosa from combined results we could calculate cell numbers for P. farcimen . This approach has overcome the challenges posed by the very limited sequence availability and low gene variability between the two species. The qPCR assay was extensively tested for specificity, efficiency and sensitivity over an entire growth cycle in both single and mixed assemblages. Comparison of cell abundance estimates obtained by qPCR assay and microscopy showed no statistically significant difference until stationary and death phases. The assay was also tested on environmental samples collected during a small Pseudochattonella bloom in Denmark in March–April 2015. It was impossible to distinguish P. farcimen and P. verruculosa by light microscopy but qPCR showed both species were present. The two methods provided nearly identical cell numbers but the assay provided discrimination and enumeration of both species.